Severe anaphylactic reaction to cisatracurium during anesthesia with cross-reactivity to atracurium - Linauskienė, Kotryna (Open Med (Wars), 2020)
A case of a severe anaphylactic reaction during general anesthesia was reported. Despite the high suspicion for cefuroxime as a trigger of the anaphylactic reaction, cisatracurium emerged being the culprit drug. This case illustrates the importance of testing all drugs used during procedures/operations, trying to find a culprit of anaphylaxis.